The creeping man [anglicky] - Doyle, Arthur Conan Sir 1859-1930; Baudet, Stephanie, 1945- (The Sherlock Holmes children's collection, 2021)
If conveniet, come to Baker Street at ONCE. If incovenient, come anyway. Holmes. When Watson rushes to Baker Street only to find it is for a case about a professor´s misbehaving dog, he is not pleased...